Appointing Officials in Local Authorities in the Arab Society in the State of Israel - Rami SAFFURI (Cross-Cultural Management Journal)
This paper examines the main factors influencing the election and appointment of officials in Arab local authorities in Israel. The election and appointment of officials in Arab local authorities in Israel face significant challenges rooted in social, economic, bureaucratic and political factors. This paper reviews key challenges such as political and clan-based influences, budgetary constraints, a shortage of skilled professionals, governance instability, violence and threats and against officials, and bureaucracy. Addressing these challenges requires comprehensive governmental policies, enhanced transparency, and improved professional training to ensure the effective administration of Arab local authorities.